ASSOCIATION G.143C>T POLYMORPHISM OF GENE CTSL WITH THE FORMATION OF FATTENING AND MEAT QUALITIES IN PIGS OF THE LARGE WHITE BREED OF UKRAINE - Почерняєв, К. Ф.; Балацький, В. М.; Лядський, І. К. (Scientific Progress & Innovations, 2014)
The results of researches of the association of gene ctsl with the formation of fattening and meat qualities in pigs of the Large White breed of Ukraine are given. It has been analysed the features of gene ctsl alelofund in different populations of pigs of LW breed, it was carried out the analysis of frequencies and distribution of different genotypes. The association g.143C>T polymorphism of this gene with thick deposits of fat in the middle of the back and in area of 6-7 ribs, as well as average daily gains , thickness of the longest muscles and meat yield was studied. It has been determined the impact force g.143C>T polymorphism of gene ctsl on these traits. It was found out significant differences (P <0.05) for some of the above traits in pigs with different genotypes of gene ctsl. On the basis of the researches it was made conclusions and advanced proposals to producers.